Literasi Keuangan Perempuan Pra-Sejahtera - Sultan, Sultan; Syamsyddin, Sofyan; Ridwan, Ridwan; Junior, M. Fadil (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to determine the level of women's financial literacy and determine whether there are differences in financial literacy levels based on socio-demographics such as age, education, occupation and income. The method used in this research is descriptive with a quantitative approach with a sample of 100 people. Data collection methods through observation, questionnaires and literature study. The research results show that: 1) the financial literacy level of underprivileged women is at the Sufficient literate level and 2) there are differences in financial literacy levels based on socio-demographics such as age, education, employment and income.